Two-year quality of life after acute pulmonary embolism: results from the FOCUS study. (3rd October 2022) - Mavromanoli, A C; Barco, S; Farmakis, I T; Rosenkranz, S; Konstantinides, S V; Valerio, L
Abstract: Background/Introduction: No firm prospective evidence exists on the long-term course of disease-specific and generic quality of life (QoL) or their determinants in patients with acute pulmonary embolism (PE). Reliable data on this topic is essential for early identification of patients at risk of deviating from the expected course and prevention of clinical events affecting QoL recovery after PE. Purpose: We examined the two-year course of QoL and the impact of events occurring after the acute phase of PE in patients from the prospective multicentre FOllow-up after aCUte pulmonary emboliSm (FOCUS) study. Methods: All patients with complete QoL assessment at 3, 12 and 24 months (N=462) were included in the analysis of the two-year course of QoL; all patients with QoL assessment at 12 months, 24 months, or both (N=740) contributed to a multivariable linear mixed-effects regression for the investigation of determinants of long-term QoL. Disease-specific QoL was assessed with the Pulmonary Embolism Quality of Life (PEmb-QoL) instrument (global score: 0 = best, 100 = worst QoL), generic health-related QoL with the Euro Quality of life group (EuroQol) five-dimensions utility index (EQ-5D-5L; 0 = worst, 1 = best QoL) and the EuroQol visual analogue scale (0 = worst, 100 = best QoL). Incident events (recurrent PE, bleeding, stroke, new cancer diagnosis, and re-hospitalization) were modelled as time-varying covariates from discharge to month 12 and from month 12 to month 24. Results: Among 462 patients with complete QoL assessment [200 (43.3%) women, median age 61.5 (IQR: 49–72) years, high-risk PE 15/462 (3.2%)], the median (IQR) PEmb-QoL score at 3, 12, and 24 months was 20 (9–36), 14 (5–30) and 13 (5–28), with a similar trend across all sub-dimensions (Figure 1); the mean (95% CI) EQ-5D-5L utility index 0.86 (0.84–0.88), 0.88 (0.87–0.90) and 0.87 (0.85–0.89); the mean (95% CI) EuroQoL visual analogue scale 74.2 (72.5–75.9), 76.8 (75.2–78.4) and 76.3 (74.6–78.0). Upon multivariable analysis in 740 patients with QoL data at 12 or 24 months, QoL according to all three scales was worse in women, patients of older age, with cardiopulmonary disease, with higher BMI, and in smokers, but did not change significantly at 24 vs 12 months. Incident PE recurrence or stroke did not considerably affect any of the QoL dimensions, whereas re-hospitalization for any cause worsened disease-specific QoL, a new cancer diagnosis worsened both scales of generic QoL, and bleeding worsened generic QoL as assessed by the Visual Analogue Scale (Table 1). Conclusion: Generic and disease-specific QoL after PE improved in the first year and then plateaued in the second year. Disease-specific QoL was adversely affected by re-hospitalization for any cause but was robust to new cancer diagnosis and bleedings, which instead worsened generic QoL. These findings may support long-term management of patients with PE and contribute to design and interpretation of interventional studies. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer Health Care